Racewalking article archives
Unter anderem mit folgenden Artikeln: World Class Clinic training articles: What The Heck Is Fast, Legal Racewalking Technique? From The Complete Guide to Racewalking Technique and Training The Link Between Stride Frequency, Respiration Rate and Heart Rate Learn Pace to Save Your Race Things to Do When You're Not Racewalking The Importance of Shin and Ankle Strength for Racewalkers What to Do When Racewalking Gives You the Creeps Dynamic Flexibility Drills for Racewalkers The Training Pyramid The Perfect Training Schedule Periodization Basics Tapering and Race Preparation for Racewalkers What About Shoes? A SCARIER Method of Injury Treatment